Detection of hepatitis B virus isolates with mutations associated with immune escape mutants among pregnant women in Ibadan, southwestern Nigeria (2015)
Perinatal transmission of hepatitis B virus (HBV) and its associated immune escape mutants (IEMs), is the major vehicle through which a population of chronically infected people who serve as infectious HBV reservoirs is maintained in communities. Therefore, to assess the risk of perinatal transmission, 272 pregnant women attending ante-natal clinics in Ibadan metropolis, southwestern, Nigeria, were screened for HBsAg using ELISA technique. Samples positive for HBsAg were subjected to HBV DNA detection by PCR amplification of the S-gene and amplicon sequencing. Isolates were genotyped and subtyped using a combination of molecular techniques. Fifteen (5.5%) of the pregnant women were positive for HBsAg of which HBV DNA was detected in seven. Five of the isolates were typed as genotype E subtype ayw4 using amino acid residues at positions 122, 127, 134 and 160. Another could only be typed as genotype E subtype ayw4 by further phylogenetic analysis. The remaining one isolate did not belong to any of genotypes A – H. Three of the HBV isolates including the untypable, had mutations in the ‘a’ determinant associated with IEMs. This study confirms the endemicity of HBV, the risk of perinatal transmission and the circulation of genotype E subtype ayw4 in Nigeria. It further demonstrates the presence of IEMs in Nigeria